Four new species of Mycale (Porifera: Demospongiae: Poecilosclerida) from the Southwest Atlantic - Mácola, Rosa; Nascimento, Elielton; Pinheiro, Ulisses; Neves, Elizabeth; Johnsson, Rodrigo (Zootaxa, 2025)
Four new species of Mycale Gray, 1867 are described in shallow water environments from northeastern Brazil: Mycale (Zygomycale) odoya sp. nov., Mycale (Naviculina) oxeata sp. nov., Mycale (Paresperella) policuspidifera sp. nov. and Mycale (M.) salvadorensis sp. nov. The studied specimens were collected at Todos-os-Santos Bay, Bahia State, Brazil. They are preserved in 80% ethanol and deposited in the Porifera Collections at the Department of Zoology (UFPEPOR), Universidade Federal de Pernambuco and Museum of the Natural History of Bahia (UFBA), Universidade Federal da Bahia. Mycale (Z.) odoya sp. nov. is an arborescent sponge, with two megasclere categories, and the microscleres are palmate anisochelae in three size categories, palmate isochelae, sigmas in two size categories, toxas, raphides and micracanthoxeas. Mycale (N.) oxeata sp. nov. is a thinly encrusting sponge with transparent surface and easily detachable ‘skin’, the megascleres are composed of mycalostyles and an additional category of oxeas, palmate anisochelae in two size categories. Mycale (P.) policuspidifera sp. nov. is a thinly encrusting sponge that is yellowish in situ, subtylostyles length 165–266 µm, with tridentate or polydentate pointed ends, microscleres are serrated sigmas and palmate anisochelae in two categories. And finally, Mycale (M.) salvadorensis sp. nov. is a massive or encrusting sponge, with two mycalostyles categories and microscleres palmate anisochelae in three size categories, sigmas in two size categories and raphides in two size categories. In addition, we present a characterization of Mycale (Zygomycale) angulosa (Duchassaing & Michelotti, 1864).